Hyaluronic acid-based core-shell microneedles for staged local delivery of psoralen toward anti-inflammatory and cartilage-protective therapy of rheumatoid arthritis - Qihui Lin; Zijian Yan; Qiangyu Chen; Yongan Lin; Dan Ying; Zhuhao Tan; Zheng Liu; Mengxing Lu; Wenjing Song; Li Ren (Carbohydrate Polymers, 2026)

Dietary Saccharomyces cerevisiae culture replacement to low-fishmeal enhances growth, intestinal health, muscle quality, and Vibrio parahaemolyticus resistance for Litopenaeus vannamei - Qingxia Luo; Mpwaga Alatwinusa Yohana; Jiaron Chai; Huaxing Lin; Jiandong Chen; Honghao Jin; Beiping Tan; Qihui Yang (Animal Feed Science and Technology, 2026)

Microplastics in crustaceans imposing potential risk on human health: transferring, degradation, synergy, and metabolism - Huibin Chen; Xiaona Shen; Jingying Lin; Qihui Huang; Lan Zhao; Ruiyu Zhu; Li Li; Zhiyu Liu; Chao Zhao (Critical Reviews in Food Science and Nutrition, 2026)

Evaluation of soybean protein peptides on growth, antioxidative capacity, non-specific immunity, and disease resistance for juvenile Litopenaeus vannamei - Huaxing Lin; Shuqing He; Yuanming Yi; Xiaomin Zhang; Shiyu Kou; Qihui Yang; Beiping Tan; Shuyan Chi (Animal Feed Science and Technology, 2025)

Oxidative stress-mediated neurotoxicity of para-xylene and neuroprotection by gluconolactone in Xenopus laevis - Lu Han; Wenyi Huang; Lingyun Meng; Xinyi Duan; Yufei Wu; Qihui Lin; Xiaohua Wu; Qi Chen; Wanhua Shen (Environmental Pollution, 2025)

Biofilms on pipelines shape the microbiome and antibiotic resistome in drinking water - Wenfang Lin; Keqian Zhao; Qihui Wu; Fei Xu; Li Cui; Huirong Lin; Chengsong Ye; Xin Yu (Water Research, 2025)

Metagenomic assembly insight into the antibiotic resistance genes and antibiotic resistant bacteria in packaged drinking water system - Xiyang Xia; Qihui Gu; Ling Chen; Jumei Zhang; Weipeng Guo; Zhenjie Liu; Aimei Li; Xinhui Jiang; Meiqing Deng; Jiahui Zeng; Xiuhua Lin; Feiting Peng; et al. (Journal of Environmental Chemical Engineering, 2025)

Evaluation of Heavy Metals and Essential Minerals in the Hair of Children with Autism Spectrum Disorder and Their Association with Symptom Severity - Xulan Zhou; Xiaochun Xia; Liming Li; Yaohui Ye; Qihui Chen; Mingyue Ke; Qian Cui; Yuling He; Yiting Chen; Shaoqing Lin; Wenlong Liu; Juan Wang (Biological Trace Element Research, 2025)

Size effects of microplastics on antibiotic resistome and core microbiome in an urban river - Wenfang Lin; Shaoheng Cao; Qihui Wu; Fei Xu; Ruilong Li; Li Cui (Science of The Total Environment, 2024)

A novel multiplex PCR based method for the detection of Listeria monocytogenes clonal complex 8 - Jianheng Cheng; Shi Wu; Qinghua Ye; Qihui Gu; Ying Zhang; Qinglei Ye; Ruoqin Lin; Xinwen Liang; Zihao Liu; Jianling Bai; Jumei Zhang; Moutong Chen; et al. (International Journal of Food Microbiology, 2024)

Extract of Ginkgo biloba Leaves (EGb) Decrease Lipid Oxidation in Fish Feed and Meat and Enhance Growth and Antioxidant Capacity in Jian Carp (Cyprinus carpio var. Jian) - Gangfu Chen; Jing Xu; Min Wu; Huatao Li; Qihui Yang; Lin Feng (Fishes, 2023)
Firstly, a linoleic and linolenic acid emulsion were incubated with petroleum ether extract, ethyl acetate extract (EAE), ethanol extract and aqueous extract of Ginkgo biloba leaves. The flavonoids content, total antioxidant capacity (T-AOC) and metal-chelating ability (MCA) were determined in EGbs above. Results showed that the extracts of Ginkgo biloba leaves (EGbs) inhibited the lipid oxidation in material above. Of all of EGbs, EAE showed the strongest T-AOC, MCA and protective effects against the lipid oxidation. Next, fish feeds were incubated with graded levels of EAE. The results showed that EAE inhibited lipid oxidation in fish feeds. The optimal inclusion levels of EAE for minimizing lipid oxidation were 4.26 g kg−1 feeds. The effect of EGbs on the lipid oxidation may be closely associated with their flavonoid content. Finally, juvenile carp (14.8 ± 0.4 g) were fed with EAE at concentrations ranging from 0.0 to 6.0 g kg−1 for 60 days. Current data displayed that dietary EAE increased the growth performance of fish. This result of EAE may be ascribed to its enhancing effect on the activity of digestive and absorptive enzymes and antioxidant capacity in digestive organs of fish. Furthermore, dietary EAE decreased the hot-drying-induced lipid oxidation in fish meat through inhibiting the induction effect of hemoglobin in erythrocytes. Our study suggests that EGb can be considered as a potential natural antioxidant for fish and fish feed.

Prevalence of antimicrobial resistance in a full-scale drinking water treatment plant - Qihui Gu; Tao Lin; Xianhu Wei; Youxiong Zhang; Shi Wu; Xiaojuan Yang; Hui Zhao; Chufang Wang; Juan Wang; Yu Ding; Jumei Zhang; Qingping Wu (Journal of Environmental Management, 2023)

A pan-coronavirus peptide inhibitor prevents SARS-CoV-2 infection in mice by intranasal delivery - Lili Wu; Anqi Zheng; Yangming Tang; Yan Chai; Jiantao Chen; Lin Cheng; Yu Hu; Jing Qu; Wenwen Lei; William Jun Liu; Guizhen Wu; Shaogui Zeng; et al. (Science China Life Sciences, 2023)

Corrigendum: Effects of dietary glycerol monolaurate on growth, antioxidant capacity and lipid metabolism in cage-farmed pompano (Trachinotus ovatus) juveniles - Huaxing Lin; Beiping Tan; Qihui Yang; Shuyan Chi; Hongjie Wei; Yuancai Wu; Gyan Watson Ray; Mpwaga Alatwinusa Yohana (Frontiers in Marine Science, 2022)

Effects of Dietary Glycerol Monolaurate on Growth, Antioxidant Capacity and Lipid Metabolism in Cage-Farmed Pompano (Trachinotus ovatus) Juveniles - Huaxing Lin; Beiping Tan; Qihui Yang; Shuyan Chi; Hongjie Wei; Yuancai Wu; Gyan Watson Ray; Mpwaga Alatwinusa Yohana (Frontiers in Marine Science, 2022)
Glycerol monolaurate (GML), a representative fatty acid glyceride, was used to promote growth. This study investigated the effects of GML in diets on growth, serum biochemical parameters, antioxidant capacity, liver morphology and lipid metabolism for juvenile pompano Trachinotus ovatus . Six groups of T. ovatus (mean weight = 14.00 ± 0.70 g) were fed with six diets, containing varying GML levels of 0.00% (G0), 0.05% (G5), 0.10% (G10), 0.15% (G15), 0.20% (G20), and 0.25% (G25) for 8 weeks. Fish were reared for in floating cages (length: 1 m; width: 1 m; and height: 2 m). The highest weight gain rate (WGR), specific growth rate (SGR), and protein deposit rate (PDR) were observed in the G15 group ( P < 0.05). Hepatic glutathione peroxidase, total antioxidant capacity and superoxide dismutase activities were significantly increased in the G10 and G15 groups compared with the G0 group ( P < 0.05), whereas hepatic malondialdehyde (MDA) was significantly reduced in the G10 and G15 groups ( P < 0.05). The alkaline phosphatase activity was significantly higher in the G5, G10, G15, and G20 groups than in the G0 group ( P < 0.05), and the highest AKP activity was observed in the G15 group. Alanine aminotransferase (ALT) activity was significantly lower in the G10, G15, G20, and G25 groups than in the G0 group ( P < 0.05). The addition of GML to the feed significantly reduced triglyceride (TG) content ( P < 0.05). In comparison with the G0 group, the G15, G20, and G25 groups had significantly lower total cholesterol content and significantly higher high-density lipoprotein content ( P < 0.05). Low-density lipoprotein content was significantly lower in the G5 and G10 groups than in the G0 group ( P < 0.05). Serious vacuolation occurred in the G0 group, but the cell boundaries in all added groups were obvious, and the rate of intracellular vacuolization decreased. As the GML level increased, carnitine palmitoyl-transferase Ι mRNA level was significantly up-regulated ( P < 0.05). The expression of fatty acid synthesis in the G10, G15, G20, and G25 groups was significantly lower than that in the G0 group ( P < 0.05). The expression of sterol regulatory element-binding protein-Ι was significantly lower in the G10, G15, G20, and G25 groups than in the G0 group ( P < 0.05). Based on the broken-line model of WGR and PDR corresponding to GML levels, the optimum addition level of dietary GML was 0.14%-0.16% for juvenile T. ovatus . In conclusion, 0.15% GML significantly improved the growth performance, hepatic antioxidant ability, and lipid metabolism and protected the liver for juvenile pompano T. ovatus .

A Challenge to Conventional Fish Meal: Effects of Soy Protein Peptides on Growth, Histomorphology, Lipid Metabolism and Intestinal Health for Juvenile Pompano Trachinotus ovatus - Huaxing Lin; Beiping Tan; Gyan Watson Ray; Min Zeng; Mei Li; Shuyan Chi; Qihui Yang (Frontiers in Marine Science, 2022)
This experiment was conducted to assess the possibility of replacing fish meal (FM) with soy protein peptide (SPP) at different levels—0% (FM), 14.29% (S5), 28.57% (S10), 57.14% (S20), 71.42%(S25)—and its effects on growth, histology, gene expression related to liver lipid metabolism and intestinal immunity in juvenile pompano Trachinotus ovatus (initial mean weight = 39.88 ± 0.15 g). 600 healthy and uniformed-size fish were distributed to five groups of three replicates, each with 40 fish in each floating cage and fed twice daily for 8 weeks. Results showed that no significant difference in the growth was observed with SPP replacing FM ( P > 0.05). Serum glutathione peroxidase activity in the S10 group was significantly higher than that in the FM group, and serum malondialdehyde content significantly decreased ( P < 0.05). SPP significantly improved intestinal immunity by increasing alkaline phosphatase and lysozyme activities and up-regulating interleukin 10 and complement 4 mRNA levels while simultaneously decreasing triglyceride and total cholesterol content and down-regulating interleukin 1β mRNA expression. Villus length and muscle thickness in the S10 group were significantly higher than those in the FM group ( P < 0.05). SPP significantly improved liver fat metabolism by increasing carnitine palmitoyl transferase I mRNA levels, and down-regulating fatty acid synthesis mRNA expression ( P < 0.05). In summary, SPP substitution for FM promoted intestinal health, liver lipid metabolism and reduced liver fat accumulation for juvenile pompano T. ovatus , with no significant effect on growth performance. Based on the second-order polynomial analysis model of LYZ activity, the optimal replacement SPP level for juvenile pompano T. ovatus was 11.82%.

A survey of chloramphenicol residues in aquatic products of Shenzhen, South China - Lan Luo; Shaoyou Lu; Chengpeng Huang; Fu Wang; Yan Ren; He Cao; Qihui Lin; Zhiqiang Tan; Xiaodong Wen (Food Additives & Contaminants: Part A, 2021)

Effect of corticision on orthodontic tooth movement in a rat model as assessed by RNA sequencing - Qihui Gu; Shuyu Guo; Dongyue Wang; Tingting Zhou; Lin Wang; Zhendong Wang; Junqing Ma (Journal of Molecular Histology, 2017)

Effect of dietary potassium on growth, nitrogen metabolism, osmoregulation and immunity of pacific white shrimp (Litopenaeus vannamei) reared in low salinity seawater - Hongyu Liu; Xinjie Zhang; Beiping Tan; Yingbo Lin; Shuyan Chi; Xiaohui Dong; Qihui Yang (Journal of Ocean University of China, 2014)